1994
DOI: 10.1007/bf01974091
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin-like growth factor-l and binding protein-3 expression in oMtla-oGH transgenic mice

Abstract: Growth hormone (GH)-transgenic mice provide a model for studying hormonal regulation of gene products responsible for efficient lean growth. Insulin-like growth factor-I (IGF-I) and IGF binding protein-3 (BP-3) are two products involved in mediating the growth promoting actions of GH. Mice carrying the ovine metallothionein la-ovine growth hormone (oMtla-oGH) transgene were used to study GH regulation of IGF-I and BP-3 expression because these mice do not exhibit elevated basal oGH levels without transgene sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…Transgene activation (provision of zinc sulfate) results in a 10-30-fold enhancement of circulating GH levels (Shanahan et al, 1989;Oberbauer et al, 1992), while inactivation (removal of zinc sulfate) leads to a return to basal levels within 24 h (Shanahan et al, 1989). In addition, Chow et al (1994) have shown that activation of the oMTla-oGH transgene results in nearly a fourfold increase in plasma IGF-I levels, while levels return to control values following transgene inactivation. Thus, the oMTla-oGH line provides a model to study effects of chronically elevated levels of circulating GH as well as the consequences of removal of this stimulus.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Transgene activation (provision of zinc sulfate) results in a 10-30-fold enhancement of circulating GH levels (Shanahan et al, 1989;Oberbauer et al, 1992), while inactivation (removal of zinc sulfate) leads to a return to basal levels within 24 h (Shanahan et al, 1989). In addition, Chow et al (1994) have shown that activation of the oMTla-oGH transgene results in nearly a fourfold increase in plasma IGF-I levels, while levels return to control values following transgene inactivation. Thus, the oMTla-oGH line provides a model to study effects of chronically elevated levels of circulating GH as well as the consequences of removal of this stimulus.…”
Section: Discussionmentioning
confidence: 94%
“…While the transgene remains activated, an overall antilipogenic environment would predominate due to elevated GH. However, upon inactivation of the transgene and, presumably, a return to basal levels of GH (Shanahan et al, 1989;Chow et al, 1994), the enhanced population of adipocytes would respond by filling with triacylglycerol droplets, creating an environment of fat deposition, and eventually leading to the observed state of obesity. No evidence exists to date showing differentiation of preadipocyte cells by GH in vivo; hence this explanation is speculative, yet intriguing as it may present a model for in vivo study of the effects of GH on the undifferentiated adipocyte population.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, a considerable overlap of circulating IGFBP-3 concentrations has been observed between acromegalic patients and healthy subjects (34), although IGFBP-3 is considered a sensitive marker of somatotroph function (35,36). For ovine metallothionein 1a-ovine GH transgenic mice, an increase in serum IGFBP-3 and hepatic IGFBP-3 mRNA expression has been reported as a consequence of heavy metal-induced GH overproduction (37). In the present study, the increase in IGFBP-3, which represents the major pool for IGFs in the circulation (for review, see Ref.…”
Section: Figurementioning
confidence: 99%